Capital Markets and Non-bank Financial Institutions in Romania : Assessment of Key Issues and Recommendations for Development - World Bank (Washington, DC, 2013)
This study assesses key issues and recommendations for development, and reviews the specific changes which are necessary in four areas: structural reforms, market institutions, and infrastructure; accounting, transparency, and disclosure; market infrastructure; and credit enhancements. With only three years remaining before joining the European Union, Romania is working hard to improve its capital markets and non-bank financial institutions, which remain less developed than those in other accession countries. Strengthening these sectors has become a top priority for policymakers, whose primary objective is to ensure that the financial system is sufficiently developed to serve the growing demands of the Romanian economy.